(Re-)defining “successful aging” as the endpoint in clinical trials?: Current methods, challenges, and emerging solutions - Schönstein, Anton (The gerontologist, 2025)
“Successful aging” as defined in Rowe & Kahn’s model aims to include the major domains of aging under a single overarching concept. From here the question arises how “successful aging” itself can be implemented as an endpoint in clinical research in a way that it is compliant to methodological regulatory framework and recommendations as formulated, for example, by the United States Food and Drug Admnistration (FDA). This article discusses from an applied perspective approaches and examples of how “successful aging” as a multidomain concept can be put into measurement practice.Narrative literature review.Existing methods of merging insights from, for example, functional, social, and cognitive outcomes can fail to perform under conditions of extreme heterogeneity, as often present in samples of older adults. In research on rare diseases, the methodological approach of a Multidomain Responder Index (MDRI) has been proposed to handle heterogeneity. MDRIs may also provide a solution to combine aging outcomes from different domains into a single “successful aging” endpoint. However, strict measurement criteria will need to be fulfilled to find acceptance in decision making and validated meaningful change thresholds are a critical prerequisite.Gerontology can spearhead methodological approaches of handling multidimensional measurement under heterogeneity by validating a “successful aging” MDRI suitable for use as an endpoint in clinical research.
Veröffentlicht: 30 May 2024
Gesehen am 26.09.2025